2020
DOI: 10.1038/s41598-019-57402-x
|View full text |Cite
|
Sign up to set email alerts
|

Response of ammonia-oxidizing Bacteria and Archaea to long-term saline water irrigation in alluvial grey desert soils

Abstract: Soil nitrification via ammonia oxidation is a key ecosystem process in terrestrial environments, but little is known of how increasing irrigation of farmland soils with saline waters effects these processes. We investigated the effects of long-term irrigation with saline water on the abundances and community structures of ammonia-oxidizing bacteria (AOB) and archaea (AOA). Irrigation with brackish or saline water increased soil salinity (EC 1:5 ) and NH 4 -n compared to irrigation with freshwater, while no 3 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…The effects of salinity on the structure of AOB and AOA communities have been investigated in many previous studies [24][25]. Salinity signi cantly alters the structure of AOA and AOB communities in wetland soil [58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of salinity on the structure of AOB and AOA communities have been investigated in many previous studies [24][25]. Salinity signi cantly alters the structure of AOA and AOB communities in wetland soil [58].…”
Section: Discussionmentioning
confidence: 99%
“…Ammonia oxidation is dominated by AOA in acidic soils but by AOB in alkaline soils, because of the low survival of AOB at low pH [21][22][23]. In addition, previous studies found that copies of the amoA gene of AOB and AOA are negatively correlated with soil salinity [24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in salt tolerance or range and the populations of nitrifiers diverged in different environments. Based on molecular studies, the abundance of AOA and AOB is reported to decrease with salinity [16]. In contrast, other studies found that AOA abundance and potential nitrification rates increased under moderate salinity (10-20 ppt), while AOB abundance was negatively or not correlated with salinity [15,21].…”
Section: Introductionmentioning
confidence: 96%
“…Several studies explored the response of nitrifiers and denitrifiers communities to salinity in mangrove sediments [12], coastal wetlands [13][14][15], and desert soils [16]. In some cases, it was found that salinity harmed nitrification [17].…”
Section: Introductionmentioning
confidence: 99%